2015
DOI: 10.4103/0019-5413.143903
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis of hip

Abstract: Tuberculosis (TB) of the hip is second to spine only hence a good number of cases are visiting the medical facilities every year. Many present in the advanced stage of the disease due to delayed diagnosis. In early stages of TB of hip, there is a diagnostic dilemma when plain X-rays are negative. In the present time, diagnostic modalities have improved from the days when diagnosis was based essentially on clinicoradiological presentation alone. By the time definite radiological changes appear on plain X-ray, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 25 publications
1
40
0
1
Order By: Relevance
“…In TB endemic areas such as Papua, a therapeutic trial using the principle of treating instead of testing first is preferred when the typical clinical and radiographic features of TB are present [2]. In cases of extensive TB disease of the hip many surgical techniques are available such as arthrotomy with debridement, arthrodesis, girdlestone or total hip arthroplasty (THA).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In TB endemic areas such as Papua, a therapeutic trial using the principle of treating instead of testing first is preferred when the typical clinical and radiographic features of TB are present [2]. In cases of extensive TB disease of the hip many surgical techniques are available such as arthrotomy with debridement, arthrodesis, girdlestone or total hip arthroplasty (THA).…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of ROM as well as the reduction of pain post operatively can be obtained by regular preoperative physiotherapy [3,4]. Employment of effective anti-tubercular drugs can reduces the chances of recrudescence significantly [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the patient was well nourished, belonged to a well to do family and thus a high index of suspicion was required to diagnose such a case. Saraf SK et al, 2015, reported that the diagnosis is often delayed in the TB hip cases [8]. The endemicity of TB in India could well be a major contributor to such primary extrapulmonary XDR-TB case.…”
Section: Case Reportmentioning
confidence: 99%